Between Anthropocentrism and Anthropomorphism: A Corpus-Based Analysis of Animal Comparisons in Shakespeare’s Plays - Postolea Sorina; Caraman Lorelei (Linguaculture, 2017)
The assertion of the centrality and supremacy of man, or rather, of the idea(l) of humanity, during the Renaissance period, inevitably entailed the repudiation of the animal and the beginning of the great human-animal divide. What was seen, at the time, as the re-birth of man, was also the birth of a rampant anthropocentrism which, until the recent so-called “animal turn”“ in critical and literary studies went unquestioned. Taking this into account, one would expect to find an almost exclusive focus on the human or what is/was perceived as being human in most works from that period. Yet, surprisingly, throughout Shakespeare‘s plays, one encounters a plethora of figures of animality leaping, running, crawling, flying, swimming, or advancing, as Derrida would say, “à pas de loup”“. From dogs, bears, lions, apes and foxes to birds, fish, worms and reptiles, Shakespeare the humanist paradoxically unfolds a veritable bestiary of nonhuman presences. Using corpus-based analysis that focuses on animal similes built with the preposition “like”“ and a critical angle largely informed by posthumanist theory, we take a closer look at the forms, roles and functions of both nonhuman and human animality in Shakespeare, as well as the intricate relationship between anthropocentrism and anthropomorphism.